Free-energy calculations using classical molecular simulation: application to the determination of the melting point and chemical potential of a flexible RDX model. Issue 11 (14th December 2015) - Sellers, Michael S.; Lísal, Martin; Brennan, John K.
Abstract : Several methods are used in sequence to determine the chemical potential of atomistic RDX in the solid and liquid phases, and its corresponding melting point. Results yield the thermodynamic melting point of 488.75 K at 1.0 atm. Abstract : We present an extension of various free-energy methodologies to determine the chemical potential of the solid and liquid phases of a fully-flexible molecule using classical simulation. The methods are applied to the Smith–Bharadwaj atomistic potential representation of cyclotrimethylene trinitramine (RDX), a well-studied energetic material, to accurately determine the solid and liquid phase Gibbs free energies, and the melting point ( T m ). We outline an efficient technique to find the absolute chemical potential and melting point of a fully-flexible molecule using one set of simulations to compute the solid absolute chemical potential and one set of simulations to compute the solid–liquid free energy difference. With this combination, only a handful of simulations are needed, whereby the absolute quantities of the chemical potentials are obtained, for use in other property calculations, such as the characterization of crystal polymorphs or the determination of the entropy. Using the LAMMPS molecular simulator, the Frenkel and Ladd and pseudo-supercritical path techniques are adapted to generate 3rd order fits of the solid and liquid chemical potentials. Results yield the thermodynamic melting point T m = 488.75 K at 1.0 atm. We also validate these calculations and compare this melting point to one obtained from a typical superheated simulation technique.